The Role of Brand Image Mediation in the Influence of Electronic Word of Mouth on Purchase Intention - Zain, Rifki Warri; Vania, Amelinda (MEC-J (Management and Economics Journal), 2024)
The rapid development of the Internet in social media and e-commerce is a major challenge for entrepreneurs, especially in the local beauty product sector that is highly competitive at home and abroad. This research aims to find out the role of brand image in mediating the influence of E-WOm on purchase intention on Azarine cosmetic sunscreen products in Shopee on Malang city. The study is explanatory with a quantitative approach and a survey method conducted on 55 respondents in Malang. Sampling nonporbability with purposive sampling techniques used. Data analysis process using Partial Least Square (PLS) with Smart-PLS 3 devices. E-WOM can have a positive and significant influence on brand image and purchase intention. Brand image can have an influence over purchase intentions. as well as brand image can mediate the influence of E-WOM on purchase intention. This research can enrich an understanding of the mechanisms that affect consumer purchasing interests in the context of the digital age.